ATIVIDADE PREDATÓRIA DE EUSEIUS CITRIFOLIUS DENMARK & MUMA (ACARI: PHYTOSEIIDAE) SOBRE TENUIPALPUS HEVEAE BAKER (ACARI: TENUIPALPIDAE) - Cardoso, M.s.m. [UNESP]; Vieira, M.r. [UNESP]; Figueira, J.c. [UNESP]; Silva, H.a.s. [UNESP] (Instituto Biológico, 2020)
The rubber tree red false spider mite, Tenuipalpus heveae Baker, is an important pest of Hevea brasiliensis (Willd. ex. Adr. de Juss.) Müell. Arg. The phytoseiid mite Euseius citrifolius Dennmark & Muma has frequently been recorded on rubber tree crops. The objective of this work was to determine the predatory activity of E. citrifolius on the different life stages (egg, larva, nymph and adult) of T. heveae. The experiments were carried out in Petri dishes (9-cm diameter) containing a layer of wet cotton inside, onto which a disk of rubber tree leaf (2.5-cm diameter) was laid. The disks were taken from naturally infested leaves. Twenty specimens in the life stage that was to be tested were left on the disk and the others were eliminated; a predator life stage (larva, nymph or female) was obtained from a laboratory stock colony and put into each dish. For each tested life stage of E. citrifolius, 4 treatments (T. heveae life stages) and 20 replications were considered in a randomized block design. The observations were made after 24 hours for larvae and nymphs of the predator, and after 24, 48 and 72 hours for the females. E. citrifolius larvae and nymphs had a higher preference for T. heveae larvae followed by nymphs, eggs and adults. Within 72 hours, each predator female consumed 15.0 larvae, 14.5 nymphs, 7.4 adults or 2.2 eggs of T. heveae. It is concluded that E. citrifolius can feed on red false spider mites, the larva and nymph being the preferred stages.

O ácaro-plano-vermelho-da-seringueira, Tenuipalpus heveae Baker é uma importante praga de Hevea brasiliensis (Willd. ex. Adr. de Juss.) Müell. Arg. Entre os ácaros predadores, Euseius citrifolius Denmark & Muma tem sido frequentemente registrado nessa cultura. Este trabalho teve por objetivo determinar a atividade predatória de E. citrifolius sobre as fases de ovo, larva, ninfa e adulto de T. heveae. Os experimentos foram realizados em placas de Petri de 9 cm de diâmetro, contendo uma camada de algodão umedecido e sobre ela um disco de folha de seringueira de 2,5 cm de diâmetro, obtido de folhas naturalmente infestadas no campo. Em cada disco foram deixados vinte espécimes da fase biológica de T. heveae a ser testada, eliminando-se o restante com um estilete. Cada placa recebeu um exemplar do predador (larva, ninfa ou fêmea), proveniente de uma criação de laboratório. Para cada fase de E. citrifolius testada, foram considerados quatro tratamentos (fases de T. heveae) e vinte repetições em um delineamento inteiramente casualizado. As avaliações foram realizadas após 24 horas para larvas e ninfas do predador e após 24, 48 e 72 horas para as fêmeas. Larvas e ninfas de E. citrifolius tiveram preferência por larvas de T. heveae, seguida por ninfas, ovos e adultos. Em 72 horas, cada fêmea do predador consumiu 15,0 larvas, 14,5 ninfas, 7,4 adultos ou 2,2 ovos de T. heveae. Assim, pode-se concluir que o ácaro-plano-vermelho é uma presa aceita por E. citrifolius, que apresenta preferência pelas fases de larva e ninfa.
PREDATORY ACTIVITY OF EUSEIUS CITRIFOLIUS DENMARK & MUMA (ACARI: PHYTOSEIIDAE) ON TENUIPALPUS HEVEAE BAKER (ACARI: TENUIPALPIDAE).
Keywords: Hevea brasiliensis; pest; predator; biological control; Hevea brasiliensis; praga; predador; controle biológico